THE IMPACT OF GLOBAL CULTURAL TRENDS ON CONTEMPORARY UKRANIAN ARTISTS AND ART EDUCATION - Malezhyk, Yuliia (Theory and practice of design, 2025)
The purpose of the study is to identify the peculiarities of the influence of global cultural trends on the work of contemporary Ukrainian artists and to identify ways to integrate them into the art education system in order to update and adapt it to modern global challenges. The methodological basis of the study is a combination of interdisciplinary and integrated approaches, which allows for a comprehensive consideration of the impact of global cultural trends on the artistic practices of Ukrainian artists, as well as on the transformation of art education in the context of digitalization and globalization. The research is based on theoretical developments in the fields of cultural studies, art history, art pedagogy, sociology of culture, and media communications. The following methods were used in the study: analytical, synthetic, and cultural studies, which made it possible to comprehensively consider the issues and formulate reasonable conclusions. Results. The article analyzes how global and cultural trends, such as digitalization, street art, innovative artistic practices, and other artistic movements, are reflected in the work of Ukrainian artists and their importance for art education, in particular. Particular attention is paid to the adaptation of international trends to the local cultural context, the preservation of national identity and the formation of a unique style of Ukrainian artists in the context of globalization. Scientific novelty. The article analyzes the multifaceted impact of contemporary global cultural trends on the artistic works of Ukrainian artists and their importance for art education in general. The key trends that shape the global cultural landscape, such as the digitalization of art, the blurring of boundaries between different types of creativity, the growing popularity of socio-political art, the influence of mass culture and new media, are considered. In addition, the article predicts potential directions for the development of Ukrainian fine arts and art education, influenced by further integration into the global cultural space. The opportunities and challenges facing future generations of Ukrainian artists in the context of the dominance of global trends are discussed, as well as ways to stimulate innovation and original artistic expression. The study allows us to understand how contemporary artists in Ukraine respond to global cultural changes and in what forms they interpret them through the prism of national identity and current socio-political processes. Its practical significance lies in the possibility of using its results to update the content of art education in Ukraine in line with global cultural trends, improve the professional training of artists, facilitate their integration into the global artistic space, and formulate effective approaches to cultural policy and pedagogical practice in art institutions.